Esempi animali e pietas filiale nella Dictio 17 di Ennodio (ACME, 2023)
The Dictio 17 (= 239 Vogel) of Ennodius is a controuersia in which the declamator speaks against a son who did not provide for the care of his aged father and thus procured his death. The argument is reinforced by examples of animals – eagles and wolves – who, unlike the defendant, take care of their parents. In the example of the eagles, Ennodius exploits a theme that is widespread in the biblical exegetical tradition; in particular, he demonstrates close consonances with the version of this motif found in Paulinus of Nola (Carm. 24 Hartel). The example of wolves is more obscure; these animals are usually characterized by ferocity and rapacity, whereas in this case they show a singular benevolence towards their parents. Here again I propose some biblical precedents that may have influenced their positive description in this controuersia. We must avoid an interpretation of Dictio 17 in a purely allegorical key, but the choice of these animal examples, connoted in a strongly Christian way, allows us to identify several interpretative levels, rhetorical, moral, and spiritual.